Size at onset of sexual maturity in macrobrachium amazonicum (Heller, 1862) phenotypes: An integrative approach - Paschoal, Lucas R. P. [UNESP]; Zara, Fernando J. [UNESP] (FapUNIFESP (SciELO), 2020)
The size at the onset of sexual maturity (SOM) was determined in four hololimnetic populations of Macrobrachium amazonicum using morphometric, physiological and functional criteria. Male prawns from two populations analyzed had hypertrophied chelipeds and large body proportions, showing the presence of four morphotypes, i.e. large-size phenotype (LS). However, the other two populations showed smaller males without morphotypes, i.e. small-size phenotype (SS). The development of sexual weapons in males modulated the mating system and SOM in this species. It was verified that there is a synchrony between physiological and functional maturities in SS males. On the other hand, functional maturity in LS males occurred after physiological and morphological maturities. In females, we verified synchronization between morphological and functional maturities. The results obtained indicated that, in both sexes, physiological maturity anticipates the others criteria. There were no differences between the sequential scheme of sexual maturity for female phenotypes, being: physiological → functional ≅ morphological. However, the evaluation of sexual maturity in males must take into account the phenotype of population, since that was modulated by functional maturity. The sequential scheme for LS males is: physiological → morphological → functional, while for SS males it is: physiological = functional → morphological.
Keywords: Amazon River prawn; Morphometric variation; Reproduction; Size at maturity